Solution phase synthesis of large-area ultra-thin two dimensional layered Bi2Se3: role of Cu-intercalation and substitution. (10th January 2020) - Pradhan, Bapi; Dalui, Amit; Paul, Susmita; Roy, Dipanwita; Acharya, Somobrata
Abstract: Intercalation of high densities of guest species without affecting the host lattice is challenging. Here we report on a general solution-based synthesis route to intercalate high densities of zero-valent copper into layered Bi2 Se3 nanosheets at room temperature. We develop a solution phase synthesis route to design large area single-crystalline two-dimensional ultrathin Bi2 Se3 nanosheets with micron dimensions. Layered Bi2 Se3 nanosheets possess rhombohedral crystal structure where the Bi and Se hexagonal planes remain in close stacked configuration forming quintuple layers along the c-direction. The coupling between two quintuple layers is predominantly van der Waals type, which allows intercalating smaller guest zero-valent copper within the layers of Bi2 Se3 nanosheets. Such intercalation of guest species without affecting the lattices of Bi2 Se3 is challenging considering the change in oxidation state of copper, which limits the intercalant concentration. Additionally, we show that the use of Cu I -amine complex at high temperature reaction conditions yields Cu I substituted Cu I -Bi2 Se3 nanosheets disrupting the host lattice of Bi2 Se3 nanosheets. We have explored the role of intercalation and substitution on the electronic properties of pristine Bi2 Se3 nanosheets. Development of new synthetic strategy for the synthesis of ultra-thin larger area 2D layered Bi2 Se3 nanosheets and understanding the role of metal intercalation and substitution hold promises for fundamental understanding and energy related applications.